Liensinine Inhibits Cell Growth and Blocks Autophagic Flux in Nonsmall-Cell Lung Cancer. (1st July 2022) - Chang, Minghui; Ding, Shanshan; Dong, Xiaohan; Shang, Xiaoling; Li, Yang; Xie, Li; Song, Xingguo; Song, Xianrang
Abstract : Liensinine is a bioactive component of Plumula Nelumbinis extracted from the green embryo of the mature seeds of Nelumbonaceae and exhibits therapeutic functions and noteworthy anti-tumor effects in recent studies. However, the potential anti-tumor property and the underlying mechanisms of liensinine in nonsmall-cell lung cancer (NSCLC) have not been illustrated. In this study, we demonstrated that liensinine has the potential anti-tumor property, and it could inhibit growth of NSCLC in vitro and in vivo . In addition, we found that although it induced significant accumulation of autophagosomes, liensinine could quench them for degradation and blocked autophagic flux. Importantly, we observed that liensinine inhibited the normal function of mitochondrial energy supply and impaired the lysosomal function. This research firstly provides a possibility insight that liensinine could be a novel therapeutic strategy for NSCLC.